Freshwater and Estuarine Diatom Composition and Seasonal Variation: Influence of Environmental Factors and its Forensic Application (RevSALUS - Revista Científica Internacional da Rede Académica das Ciências da Saúde da Lusofonia, 2025)
Background: Diatoms are essential microalgae for aquatic ecosystems, sensitive to seasonal physicochemical variations such as temperature, pH and nutrients, influenced by natural and anthropogenic factors [1]. With relevant forensic applications, they aid in identifying drowning sites and geolocation [2]. Objective: This study investigates the seasonal composition of diatoms in three aquatic systems in northern Portugal, with a view to forensic applications and environmental conservation. The aim was to assess how seasonal factors (temperature, turbidity, conductivity, dissolved oxygen and nutrients) influence diatom composition and create a database supporting forensic applications. Methods: Water samples were collected seasonally between 2022 and 2023 from a stream (Asprela), an estuary (Ave River), and two private wells. Physico-chemical parameters were determined using standardized methods, while diatom identification was carried out by optical microscopy after chemical digestion. Diatoms were identified using scientific literature and an online tool. Statistical analysis correlated environmental parameters with the abundance of specific species. Results: Diatoms showed distinct seasonal variation in each environment. In the stream, differences were observed between the two sampling points, with genus such as Pinnularia predominating in more alkaline conditions. In the estuary, high concentrations of nutrients and turbidity were recorded in the autumn and spring, correlating with genus such as Melosira. The wells had a low population density, with benthic species predominating. Genus such as Navicula and Nitzschia correlated positively with conductivity and nitrites, while Gomphonema showed an affinity for oligotrophic conditions. The high levels of phosphates in the estuary highlighted the influence of local agricultural practices. Seasonal variations reflect the responses of diatom communities to environmental changes, especially turbidity and nutrient enrichment. The increase in nutrients, associated with human activities, favored species adapted to eutrophic conditions, while turbidity reduced abundance in some seasons. The correlation between diatoms and parameters such as nitrites and conductivity suggest their usefulness in environmental and forensic analysis. However, discrepancies, such as the unexpected correlation between Navicula and conductivity, indicate the need for further investigation. Conclusions: This study demonstrated the relevance of diatoms as bioindicators and reinforced their applicability in forensic investigations. The creation of a comprehensive database with seasonal information could improve the accuracy of forensic analysis, particularly in cases of drowning and geographical tracking. Future studies should explore the impacts of climate change on the distribution of diatoms, considering their ecological and forensic implications.